Strategic development and SWOT analysis of specialized children services in public libraries - Nugraha, Aufa Fikri; Rahmanisa, Naila Adinda; Nova, Aida Nelfauza; Silvana, Hana; Ramadhan, Suci Yanti (Jurnal Informatio, 2026)
Background: Public libraries play a strategic role in fostering children’s literacy and lifelong learning by providing services that are inclusive, engaging, and developmentally appropriate. However, children’s library services in many public libraries still face structural and managerial challenges that limit their effectiveness.Purpose: This study aims to evaluate the quality of children’s services at the Kabupaten Bandung Library and Archives Office (Dinas Perpustakaan dan Kearsipan Kabupaten Bandung) and to formulate development strategies based on identified conditions. This study fills a research gap by employing SWOT analysis specifically to evaluate children’s services in Kabupaten Bandung public library.Methods: This research employed a descriptive qualitative design with a field research approach. Data were collected through direct observation and semi-structured interviews with librarians involved in children’s services. The aspects examined included collections, facilities, programs and activities, as well as interactions between librarians and child users. Data were analyzed using the SWOT framework to identify strengths, weaknesses, opportunities, and threats affecting children’s services.Results: The results indicate that the library has provided basic child-friendly facilities and implemented several literacy-oriented programs. Nevertheless, key challenges remain, including limited inclusive and foreign-language collections, the absence of a dedicated children’s librarian, and programs that are largely dependent on external requests rather than internal planning. Based on the SWOT analysis, several strategic recommendations are proposed, such as strengthening and diversifying collections, improving child-friendly and inclusive facilities, enhancing cross-sector collaboration, and establishing specialized children’s librarian roles. Conclusion: A structured and strategic approach is essential to ensure the sustainable development of children’s services and to strengthen the role of public libraries as responsive literacy spaces for children.